CAPITAL SOCIAL E REDES: uma análise dos efeitos do Programa de Aquisição de Alimentos da Agricultura Familiar em municípios diferenciados no Estado de Goiás - Leandro de Lima Santos (Universidade Federal do Maranhão, 2016)
This research presents an investigation on how the effects / results of a public policy may be influenced by social capital elements formed by networks. In this sense, there was a comparative analysis of Family Farming Food Acquisition Program (PAA) set up in different cities in the state of Goiás, Itapuranga and Silvânia. The central contribution of the research is to identify and understand the formation and the types of social networks involving the program's actors in each location, as legacies of historical, social and political link, and what is its connection with the results of PAA. The articul ation and dialogue between the social cohesion of networks formed and the effectiveness of a government program which in turn are linked to the productive characteristics, environmental and economic of these beneficiaries. Brings finally the discussion of social networks and their significance to these effects.